Peran pendidikan gizi dalam menanggulangi beban ganda malnutrisi - Alfina, Riza (Maliki Interdisciplinary Journal, 2026)
Implementing a healthy lifestyle currently faces significant challenges due to lifestyle changes and easy access to nutrient-poor foods. This has led to the emergence of the "Double Burden of Malnutrition" phenomenon, where malnutrition conditions such as stunting and wasting occur simultaneously with increasing obesity rates, both at the population and individual levels. Therefore, nutrition education plays a strategic role as a primary tool in changing community habits. Through nutrition education, the public is expected to be able to choose foods that are not only nutritionally balanced but also meet halal and thoyyib (good) requirements. Furthermore, nutrition education must include the skill of reading product labels, so that the public is more aware of sugar, salt, and fat content. Nutrition education starting at an early age through personalized and innovative communication methods has proven effective in strengthening health awareness. Therefore, nutrition education is a crucial investment in developing high-quality, healthy, and globally competitive human resources in the future.